If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4(2x + -3) = 15 Reorder the terms: x + 4(-3 + 2x) = 15 x + (-3 * 4 + 2x * 4) = 15 x + (-12 + 8x) = 15 Reorder the terms: -12 + x + 8x = 15 Combine like terms: x + 8x = 9x -12 + 9x = 15 Solving -12 + 9x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 9x = 15 + 12 Combine like terms: -12 + 12 = 0 0 + 9x = 15 + 12 9x = 15 + 12 Combine like terms: 15 + 12 = 27 9x = 27 Divide each side by '9'. x = 3 Simplifying x = 3
| 0=x^2-7x-7 | | 20y^2+29y+6=0 | | -(8y+5)-(-7y-8)=-1 | | 6(4x-9)=2(12x+8) | | 13-8x=73-29x | | 20x^2=45x | | -4x^2-20x-25=0 | | 0.18(12)+0.02x=0.06(24+x) | | 8+19n-3=7n+89-2n | | 2(3x-4)=5(8-2x) | | 7(2x-1)=3(15-4x) | | 6x^2+18=-21x | | -2v^2-5v-3=0 | | 1000=x+(x*.8)+(x*.3) | | 3.5q-1.4-5.9q=-3.4q-4.4 | | 1000=x+(x*.8)+(x*.5) | | -5y+4=-6y+5 | | 3x^2-14x=-18 | | 12x+6-3=11x-3 | | -10+3+6=-10 | | -4v^2-13v-3=0 | | -(8y+3)-(-7-4)=-1 | | 0.30(18)+0.05x=0.15(18+x) | | 8-4x+-6x=50 | | 4(2x-1)=2(3x+8) | | 4(3x+12)=2(2x+4) | | 1000=x+(x*.8) | | 3=2e^4x | | 9(x-36)=18 | | 2(x+4)=6(2x+3) | | 7(4x+6)+15= | | 4x-5=11-89 |